Surface Electromyography Unveil the Relationship between Masticatory Muscle Tone and Maloclusion Class I & II in Javanese Ethnic Patient - I Gusti Aju Wahju Ardani, - (Ektodermal Displazi Grubu-Türkiye, 2020)
Aim to evaluate the difference of masticatory muscle activity of Malocclusion Class I and Class II malocclusion in Javanese ethnic patient detected by surface electromyography (sEMG). Observational analytic cross-sectional study was done. The sample consisted of 16 patients, 18-21 years-old taken by the total sampling. The classification of malocclusion based on Angle’s malocclusion classification then divided into Class I malocclusion (ANB<4º) and Class II Malocclusion group (ANB>4º) based on cephalometric, study models and intra-oral examination (n=8). The cephalometry was traced using the Orthovision™ digital program and then the anatomical points are determined. The measurement of muscle activity was recorded by means of sEMG. Determine the installation of black-red electrodes according to the direction of muscle contraction from origo to insertio. Pairing the electrode pad then parallel to the muscle belly with muscle fibers with a distance of 1 cm between the electrodes and ground plug. Select the feedback mode and sensitivity according to muscle strength. The right and left side of masseter, temporalis, suprahyoid muscles activity was examined. Mann-Whitney analysis (p<0.05) was done based on homogenity and normality data test (p>0.05). Only the right side of temporal muscle activity was significantly different in Class I and Class II malocclusions in Javanese ethnic patient (p=0.0001). Meanwhile, the masseter and suprahyoid muscles right side, have no significant differences were found in Javanese ethnic patient (p=0.99). Therefore, there was no significant different in left side of temporalis (p=0.11), masseter (p=0.99) and suprahyoid (p=0.104) muscle activity between malocclusion class I and II in Javanese ethnic patient. Temporalis, masseter, and suprahyoid muscle activity detected by sEMG have no significant difference in malocclusion Class I and II in Javanese ethnic patients.